Behaviour of concrete beams reinforced jute fiber mat - Lee, Yen Wah (2017)
Jute fiber has recently become attractive to researchers, engineers and scientists as a potential to be a substitute reinforcement in reinforced concrete. The use of the jute fiber fabric and fiber reinforced polymer (FRP) as the reinforcement materials has gained popularity due to their mechanical strength and inexpensive cost. This research presents a study of the mechanical properties of Jute fibre mat (JFM) as well as the behaviour of the JFM-reinforced concrete beam. Jute fibres were chemically treated with the 5% (w/v) sodium hydroxide, NaOH over 4 hours duration at room temperature, thus the single fiber test was conducted to study the differences between treated and untreated fiber filament in term of uniaxial tensile strength and the elongation. Subsequently, the treated jute fiber was used in the fabrication of the JFM with a different fibre volume ratio of 15%, 20%, 25% and 30%. All the JFM samples were undergone the tensile and flexural test by using the Universal Testing Machine (UTM) to determine the optimum fibre volume ratio. In terms of structural properties, a total of six (6) concrete beams with compressive strength of 25 MPa were tested to failure under three-point loading, which includes two control beams (CB), two JFM reinforced beams (JFMB) and two beams that reinforced by two steel bars with a diameter of 10 mm (SB). The beam had a cross section of 100 mm in both width and depth as well as a total length of 500 mm. By comparing with the untreated fiber, the maximum tensile strength of treated jute fiber with sodium hydroxide solution was found to increase by 71.3%, whereas the elongation at break decreased by 44.3%. In terms of mechanical properties, the JFM with 25% fibre content showed the highest maximum tensile strength of 73.2 MPa, while the 15% of fibre content has the highest flexural strength of 75.2 MPa. JFM with 25% fibre content was considered as the optimum fibre volume and used as the reinforcement mat in this research. From the three-point loading test result, the JFM reinforced concrete beams (JFMB) manage to sustain the ultimate load of 10.60 kN with the deflection of 0.6 mm. Although, the load capacity of beams JFMB is 26.34% higher than the beams CB, only achieves 28.7% strength of beams SB. The JFM beams was failed in a brittle manner under bending with a vertical crack in the tension zone.